Non-thermal atmospheric pressure plasma: An alternative method to enhance the seed quality in long bean-KPN (Vigna unguiculate L.) seeds. (2022) - Hendeniya, Nayanathara; Sandanuwan, Thisara; Attygalle, Dinesh; Amarasinghe, D.A.S.; Weragoda, Sampath; Ranaweera, Bandula; Ratnayake, Kamani; Lalanka, Malki
Abstract: Non-thermal atmospheric pressure plasma treatment has emerged as a promising potential seed quality enhancement method over recent years. This study focuses on the effect of atmospheric pressure plasma treatment on seed germination and growth of Long Bean-KPN ( Vigna unguiculata L.) seeds under laboratory conditions. In this study, the Long Bean seeds were exposed to a dry air non-thermal atmospheric pressure plasma for different periods between 4 and 10 min to study its effect on seed germination and growth behavior. It was observed that Germination percentage and Seed Vigor Index were negatively affected by plasma treatment for more than 6 min. The performance of seeds treated for 4 min had a slight improvement in germination over the control specimen, while it showed a significant improvement in average seed vigor index. The study confirmed that non-thermal atmospheric pressure plasma treatment can be stimulatory for seed germination and growth of Vigna unguiculate L. seeds if exposed to plasma for periods less than 4 min and it can be inhibitory for the purpose if exposure time exceeds 6 min.